Behavioral finance : investors, corporations, and markets - Baker, H. Kent; Nofsinger, John R. (The Robert W. Kolb series in finance, 2010)
"Behavioral finance has increasingly become part of mainstream financeh?elping to provide explanations for our economic decisions by combining behavioral and cognitive psychological theory with conventional economics and finance. Filled with in-depth insights and practical advice, this reliable resourcep?art of the Robert W. Kolb Series in Financep?rovides a comprehensive view of behavioral finance by discussing the current state of research in this area and detailing its potential impact on investors, corporations, and markets." "Comprising contributed chapters by distinguished experts from some of the most influential firms and universities in the world, Behavioral Finance provides a synthesis of the essential elements of this discipline including psychological concepts and behavioral biases; the behavioral aspects of asset pricing, asset allocation, and market prices; investor behavior, corporate managerial behavior, and social influences. Divided into six comprehensive parts, it skillfully:" "Describes the fundamental heuristics, cognitive errors, and psychological biases that affect financial decisions" "Discusses market inefficiency and behavioral-based pricing models" "Explores corporate and executive behavioral finance and examines the behavioral influences involving their investment and financing decisions" "Addresses how behavioral finance applies to individual and institutional investors' holdings and their trading endeavors" "Shows how cultural factors and societal attitudes affect markets" "Behavioral Finance contains the latest information from some of the leading practitioners and academics in this field. Engaging and accessible, this book provides a clear understanding of how people make financial decisions and their effects on today's markets."